Influence of Swimming Training Session on Selected Saliva Components in Youth Swimmers - Grzesiak-Gasek, Iwona; Kaczmarek, Urszula (Frontiers in Physiology, 2022)
Exercise may induce many changes in biochemical parameters of the saliva. Thanks to non-invasive access, saliva can be used as a diagnostic material in physical activity monitoring. The aim of the study was comparison of selected salivary components in swimmers before and after training session. 40 male subjects aged 12-15, out of whom 30 were competitive swimmers and 10 control were involved in the study. Salivary samples were collected from all subjects in the morning, and in the afternoon; from the swimmers, they were also collected before and after the workout. Salivary flow rate-V, pH, total protein-P, alpha-amylase-Amy, salivary peroxidase-SPO, cortisol-C, total antioxidant status-TAS, sialic acid (free-FSA, bound-GSA, total-TSA), calcium-Ca, magnesium-Mg were measured. The swimmers assessed the workout intensity of training session using the RPE Foster’s scale. The circadian rhythm pattern of some salivary components and differences after training were found. In swimmers after the morning exercise significant increase of P (0.83±0.27 vs 1.10±0.58g/L), Amy (64.91±70.86 vs 87.07±92.46IU/L), Ca (3,83±1,33 vs 4.99±2.24mg/L), Mg (0.52±0.32 vs 0.73±0.34mg/L), TAS (0.64±0.27 vs 0.72±0.26mmol/L) and decrease V (0.47±0.37 vs 0.36±0.22mg/min), C (5.86±5.00 vs 3.54±5.07µg/ml) were found. After the afternoon training significant increase of pH (7.13±0.33 vs 7.27±0.24), Amy (111.53±120.13 vs 130.91±161.14IU/L), Ca (3.72±1.34 vs 4.61±1.58mg/L), Mg (0.48±0.28 vs 0.60±0.39mg/L), TSA (5.64±3.78 vs 6.10±3.08mg/L), GSA (3.00±3.06 vs 3.38±2.26mg/L), and decrease of V (0.63±0.63 vs 0.49±0.39ml/min) were noticed. Before training in the morning in the swimmers significantly higher of V (0.47±0.37 vs 0.26±0.15mg/min), TAS (0.64±0.27 vs 0.40±0.16mmol/L), and lower pH (7,01±0.46 vs 7.53±0.33), P (0.83±0.27 vs 1.86±1.28g/L), Amy (64.91±70.86 vs 146.56±114.45IU/L) compared to the control were found. In the afternoon in swimmers before training session significantly lower pH (7.13±0.33 vs 7.53±0.49) and Amy (111.53±120.13 vs 170.98±107.72IU/L) ) in comparison to the control were noticed. The RPE scores were negatively correlated with V (rho=-0.500, p=0.05 and pH (rho=-0,382, p=0,03) measured after the morning session and after the afternoon training with V (rho=-0.570, p=0.01) and Ca (rho=-0.401, p=0.08). The levels of salivary flow rate, alpha amylase, cortisol, calcium, magnesium were associated with swimming training session, and showed circadian variation without a significant effect on their responses to exercise.